Wound of ureter and cava - Balboa, Oscar; Melognio, Silvio; Durante, Arturo (Cirugía del Uruguay, 1974)
A patient had suffered bullet wounds in the lower vena cava and right ureter and diagnosis was not esta blished immediately. In such cases it is convenient to attempt a primary approach on retroperitoneal hematomas.